Efektivitas Pemasaran Jasa Photography Melalui Media Sosial Instagram di Bali - I Ketut Pasek Wisuda (Universitas Pendidikan Nasional, 2019)
ABSTRACTThe purpose of this study was to determine the effectiveness of photography services marketing using Instagram social media in Bali Province. Data collection techniques used interview and observation methods. Stages in data analysis include data reduction (data reduction), presenting data (data display) and drawing conclusions and verification (conclusion drawing / verification). Based on the results of research conducted on the Five Photographers who use Instagram social media as a promotional media which has followers or followers of more than 20,000 in the Province of Bali, the conclusion is the use of Instagram social media to popularize and promote photography services, is quite effective and also generate additional income for informants. All informants also said that using the marketing strategy using Instagram was more useful than using other conventional methods. But for the upper class segmentation, the promotion must be accompanied by making a website to reach a wider market place.